A two-photon fluorescent probe for viscosity imaging in vivo. Issue 15 (13th March 2017) - Ning, Peng; Dong, Pengyu; Geng, Qian; Bai, Lei; Ding, Yaqi; Tian, Xiaohe; Shao, Rong; Li, Lin; Meng, Xiangming
Abstract : A quinoline-based two-photon fluorescent probe (MCN ) was developed for viscosity imaging in vivo . Abstract : A new two-photon fluorescent probe (MCN ) for viscosity imaging was developed based on a 6-substituted quinoline framework.MCN showed an excellent "off–on" fluorescence response ( ca. 90-fold enhancement) with viscosity increasing in the glycerol–water viscosity system.MCN showed great sensitivity to viscosity ( R 2 = 0.98, x = 0.65), which gave rise to cell imaging for micro-viscosity or real-time cell imaging during apoptosis with low cytotoxicity under two-photon excitation ( λ ex = 800 nm). Fluorescence lifetime imaging (FLIM) of living HeLa cells stained withMCN revealed that the intracellular average viscosity value was 73.45 ± 21.55 cP in cytosol. Imaging in living tissue slices indicated thatMCN can work in deep tissue (∼130 μM) under two-photon excitation. Moreover, MCN also showed the capacity for in vivo imaging viscosity in zebrafish with obvious fluorescence emission.